Analysis of Effectiveness in Improving the Welfare of Fishermen Communities in Majene Regency (Study on the Maritime and Fisheries Business Actor Card Program) - Aulya Rahma T; Agung Haryono; Lisa Rokhmani (International Journal of Economics, Business and Innovation Research, 2023)
To protect and improve the welfare of fishing communities, the government through the Ministry of Maritime Affairs and Fisheries created a program contained in the Republic of Indonesia's KKP Regulation Number 39/Permen-KP/2017 concerning the KUSUKA Card which is a form of card integration and data for marine and fisheries business actors. This study aims to analyze the effectiveness of the KUSUKA Card program in improving the welfare of fishing communities in Majene Regency. This research uses a qualitative type with a case study approach. The results of the study show that (1) The understanding of the KUSUKA Card program in fishing communities in Majene Regency is only limited to the requirements in administering and replacing Fisherman's Cards. (2) The targeting of the KUSUKA Card program for fishing communities in Majene Regency has been successful in data collection on marine and fisheries business actors. (3) Timeliness in the distribution of KUSUKA Cards in Majene Regency has not been fully realized. (4) The objectives of the Kusuka Card program in Majene Regency have been achieved in terms of data collection to update the fishermen's database. (5) The real changes felt by fishing communities have not run optimally. So far, the goal to be achieved in improving the welfare of fishing communities in Majene Regency has not been implemented appropriately